Implementasi Hukum Dalam Penyalahgunaan Obat Tramadol Pada Remaja - Ningsih, Nur; Dhahry, Irsyad; Hanafie, Nurharsyah Khaer (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2023)
This study aims: (i) To find out how far the implementation of legal provisions related to tramadol drug abuse in adolescents in Bima district. (ii) To find out the appropriate sanctions related to tramadol drug abuse in adolescents in Bima Regency. This research method uses a type of qualitative research with a descriptive approach, the data sources used are primary and secondary data, using observation, interview and documentation data collection techniques and using source triangulation analysis techniques. Research results show that, (i) Implementation of legal provisions related to tramadol drug abuse in adolescents in Bima Regency is conducting counseling related to the provisions of the Narcotics and Health Law, as well as holding religious activities and placing banners containing the crime of Narcotics Abuse, which already includes including Tramadol medicine, involving Bhabinkamtibmas, village heads, community leaders, religious leaders, youth leaders and community elements. (ii) Appropriate sanctions related to tramadol drug abuse in adolescents in Bima Regency, namely the Narcotics Unit and the Bima Regency Health Office put juridical emphasis and implementation of health regulations. As explained in article 197 below: If a person deliberately produces or distributes and trades and uses illegally, for his actions, the alleged perpetrator is subject to Article 196 in conjunction with Article 197 of Law Number 36 of 2009 concerning Health with a penalty of 10 to 15 years in prison and also in Law Number 35 of 2009 concerning Narcotics namely in articles 111 to article 121. Thus the efforts made by the Bima Regency government have been quite optimal.